2006
DOI: 10.1038/sj.ijo.0803244
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of attrition in the treatment of obesity: clues from a structured telephone interview

Abstract: Objectives: To investigate the causes of attrition reported by obese patients treated by medical centres. Design: Observational study. Setting: Obese patients enrolled in a long-term study involving 18 Italian medical centres. Participants: A total of 940 obese patients (727 female; mean age, 49 years; mean BMI, 38.6 kg/m 2 ). Measurements: Causes of attrition reported by dropouts during a structured telephone interview. Results: After a median observation period of 41 months (range, 25-50), 766 of 940 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
129
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 26 publications
(35 reference statements)
12
129
2
3
Order By: Relevance
“…A motivational interview (9) may be the method of choice for helping patients to resolve their ambivalence and hence change their behaviour. The lack of effective counselling might also have affected their motivation, because, although not directly comparable to our finding, the lack of motivation has been proposed as being the single most important reason for attrition in the treatment of obesity (10,11). In the LITE study, we did not measure the participants' self-motivation and adherence to lifestyle changes, for example, by using the Self-Motivation Inventory (12), since this would need to first be translated for and then validated in our population.…”
Section: Discussionmentioning
confidence: 38%
“…A motivational interview (9) may be the method of choice for helping patients to resolve their ambivalence and hence change their behaviour. The lack of effective counselling might also have affected their motivation, because, although not directly comparable to our finding, the lack of motivation has been proposed as being the single most important reason for attrition in the treatment of obesity (10,11). In the LITE study, we did not measure the participants' self-motivation and adherence to lifestyle changes, for example, by using the Self-Motivation Inventory (12), since this would need to first be translated for and then validated in our population.…”
Section: Discussionmentioning
confidence: 38%
“…A follow-back study of these women suggested that concerns about caregiving were very important, and that physical activity was simply a lower priority [37]. Successful retention has been accomplished with greater staff time, support and attention, social support and time with peers during the intervention, interventions with less time commitment, increased remuneration, commitment to finish, and understanding of the importance of the study as reasons for completion, suggesting possible additional avenues for improved retention strategies [12,17,23,[55][56][57][58]. Although many of these considerations were included in this study, it is clear that there is still room for future studies to investigate whether participant burden can be minimized sufficiently to include harder to reach and underrepresented populations or whether different kinds of strategies are needed that simply remove individual, participant burden by focusing on policy, environment, and systems.…”
Section: Original Researchmentioning
confidence: 99%
“…Representativeness is a particularly important consideration as the findings can only be generalized to those represented in the study, affecting the practicality of translating research to action. People from lower socioeconomic status backgrounds and ethnic minorities may be more likely to dropout compared to wealthier and white populations, often attributed to dissatisfaction with the research experience such as lack of motivation, dissatisfaction with results, feelings of abandonment, a lack of encouragement or poor social support, the belief one can accomplish the study goal without assistance, other personal reasons (e.g., work interference, lack of time, stress), healthcare system issues (e.g., lack of flexibility in scheduling appointments), and study design (e.g., difficult study regimes) [1,[22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…The observed attrition rate is higher than that reported by Dalle et al , but it is comparable to rates observed in other studies in Italy and Australia. 14,20,21,22 Majority of our study subjects were youthful, below the age of 40 years and may have been much younger when they engaged in the previous weight loss methods.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 This is because when these unrealistic goals are not met, subjects become dissatisfied and de-motivated to continue with a program. 21 Overweight and obese individuals need education on setting realistic weight loss goals and the health benefits associated with just a 5-10% reduction in body weight, a goal that is achievable and sustainable. 27,28 Programs will be well accepted and followed through until the achievement of desired weight goal if they provide realistic diet plans that are more practical to the client in terms of closeness to their original dietary habits, are interesting, results oriented within a reasonable time length, safe, and motivates the client to continue in the program.…”
Section: Discussionmentioning
confidence: 99%